Assessment of Individual Radiosensitivity in Inhabitants of Takandeang Village - A High Background Radiation Area in Indonesia - D. Ramadhani; S. Purnami; S. Nurhayati; M. Lubis; D. Tetriana; W. Mailana; K. D. Purwanti; E. Pudjadi; I. Kashiwakura; R. Okazaki; M. Syaifudin (PPIKSN-BATAN, 2019)
People living in high background radiation area (HBRA) possibly developed the radioadaptive response (RAR) phenomena. Mamuju area in West Sulawesi Indonesia also known as the HBRA in Indonesia due to high natural uranium contents. It is possible that RAR was developed in Mamuju inhabitants. To prove this hypothesis, here in this study evaluation of the individual radiosensitivity in Takandeang Village, Mamuju inhabitants using G2 micronucleus (MN) assay was conducted. Association between blood groups and TP53 Arg72Pro polymorphism with individual radiosensitivity also evaluated in this study. Using G2 MN assay we assessed the individual radiosensitivity of Takandeang Village inhabitants and control samples. For each sample, three parameters were calculated. The spontaneous (baseline) MN number, MN number after 0.5 Gy in vitro irradiation and radiation induced MN were calculated to predict the individual radiosensitivity. The radiation induced MN was deﬁned by subtracting the spontaneous MN number from the MN number after irradiation. The mean and SD of the number of micronucleus induced by radiation found in control group (CG) was set as the cut-off value to determine the individual radiosensitivity in all samples. The radiation induced MN higher than the mean CG + 1SD CS was scored as 1, indicating a milder radiosensitive phenotype, whereas a result higher than the mean CG + 2SD CG was scored as 2, and indicated a more severe radiosensitive phenotype. When the individual value was lower than the mean CG + 1SD CG, a score of 0 was attributed to the tested subject. Results showed that four individuals in Takandeang Village inhabitants were having a milder radiosensitive phenotype, whilst the other was categorized as normal radiosensitive. The similar finding also found in control samples. Our study failed to find a correlation between radiosensitivity and blood group also the TP53 Arg72Pro polymorphism. Overall our study revealed the possibility of RAR phenomena in Takandeang Village inhabitants. Further investigation using a different point of radiation dose value and larger sample number should be performed to validate this study results.